In vitro innate immune cell based models to assess whole cell Bordetella pertussis vaccine quality: A proof of principle. Issue 2 (March 2015) - Hoonakker, M.E.; Verhagen, L.M.; Hendriksen, C.F.M.; van Els, C.A.C.M.; Vandebriel, R.J.; Sloots, A.; Han, W.G.H.
Abstract Lot release testing of vaccines is primarily based on animal models that are costly, time-consuming and sometimes of questionable relevance. In order to reduce animal use, functional in vitro assays are being explored as an alternative approach for the current lot release testing paradigm. In this study, we present an evaluation of APC platforms assessing innate immune activation by whole cell Bordetella pertussis (wP) vaccines. Primary monocytes, monocyte-derived DC (moDC) and human monocyte/DC cell lines (MonoMac6 and MUTZ-3) were compared for their capacity to respond to wP vaccines of varying quality. To produce such vaccines, the production process of wP was manipulated, resulting in wP vaccines covering a range of in vivo potencies. The responses of MUTZ-3 cells and primary monocytes to these vaccines were marginal and these models were therefore considered inappropriate. Importantly, moDC and MonoMac6 cells responded to the wP vaccines and discriminated between vaccines of varying quality, although slight variations in the responses to wP vaccines of similar quality were also observed. This study provides a proof of principle for the use of in vitro APC platforms as part of a new strategy to assess wP vaccine lot consistency, though careful standardisation of assay conditions is necessary.